Pilot decontamination in massive MIMO system combining time-shifted and cell sectorization pilot assignment - Xin-lei SONG; Lin YANG; Jia-liang DU (Tongxin xuebao)
Pilot contamination is appeared in massive MIMO (multiple input multiple output) system when using the same pilot sequences at different cells to get the channel state information.It becomes a bottleneck problem of massive MIMO when the number of antenna goes infinite.In order to dealt with pilot contamination,a new TS-CSPA joint scheme was proposed.This scheme can mitigate pilot contamination by reduce the reuse of pilot sequence through the time domain and space domain.And the closed-form expression for the achieved rates and signal to interference plus noise ratio(SINR) to verify the advantages of the proposed scheme were given.Numerical results show that significant performance gains to mitigate pilot contamination problem compared to other methods.